Synthesis of a Biodegradable Polymer of Poly (Sodium Alginate/Ethyl Acrylate) - Flores-Hernández, Cynthia G. (Polymers (Basel), 2021)
The objective of the study was to obtain a new biodegradable graft polymer by performing two chemical processes: first, a transesterification reaction between carboxylic acid’s salt and ethyl acrylate’s ester, followed by polymerization of the vinyl group from the ethyl acrylate monomer via free radicals. The copolymer’s FTIR shows an absence of ethyl bands, while the characteristic band of pyranose is maintained, which confirms the monomer’s graft. TGA analysis shows that sodium alginate had three decomposition temperatures: 103 °C due to dehydration, 212 °C associated with the destruction of glycosidic bonds, and 426 °C due to conversion of alginate into Na(2)CO(3). The copolymer presents four processes at different temperatures, i.e., evaporation of alcohol at 65 °C, decomposition of ungrafted alginate at 220 °C, copolymer decomposition at 298 °C, and degradation of fragments into carbonate at 423 °C. The evaluation of the action of fungal growth on the copolymer was higher than 50%, which means it is an excellent material to be biodegraded.